2007
DOI: 10.1177/0891242406296326
|View full text |Cite
|
Sign up to set email alerts
|

Finding an Impact of Preservation Policies: Price Effects of Historic Landmarks on Attached Homes in Chicago, 1990-1999

Abstract: The impact of landmark designation on prices of the property and its neighbors sits at the core of the policy debate and empirical research on historic preservation. Yet these studies suffer from serious methodological limitations and biases. First, as important unobserved characteristics likely correlate with landmark designation, an omitted-variable bias results. Second, if designations depend on property values or neighborhood housing market conditions, the endogenous selection process further undermines in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 28 publications
4
82
1
2
Order By: Relevance
“…Beyond this threshold, evidence for positive effects is weak at best. This is significantly less than previous studies have found in terms of the internal price effect of particular architectural styles and design features (up to about 20%, see Asabere, et al, 1989;Moorhouse & Smith, 1994;Vandell & Lane, 1989) and the external price effect of large scale iconic sports facilities (up to about 15%, see Ahlfeldt & Kavetsos, 2011;Ahlfeldt & Maennig, 2010b), but significantly more than the existing evidence for the effect of an additional historic landmark in close vicinity (0.14-2.8%, see Ahlfeldt & Maennig, 2010c;Lazrak, et al, 2010;Leichenko, et al, 2001;Noonan, 2007).…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…Beyond this threshold, evidence for positive effects is weak at best. This is significantly less than previous studies have found in terms of the internal price effect of particular architectural styles and design features (up to about 20%, see Asabere, et al, 1989;Moorhouse & Smith, 1994;Vandell & Lane, 1989) and the external price effect of large scale iconic sports facilities (up to about 15%, see Ahlfeldt & Kavetsos, 2011;Ahlfeldt & Maennig, 2010b), but significantly more than the existing evidence for the effect of an additional historic landmark in close vicinity (0.14-2.8%, see Ahlfeldt & Maennig, 2010c;Lazrak, et al, 2010;Leichenko, et al, 2001;Noonan, 2007).…”
Section: Resultscontrasting
confidence: 57%
“…Lately, studies have also started to consider the external benefits of landmarks which are more directly related to this study. Looking at densities within census tracts (Coulson & Lahr, 2005), block groups (Noonan, 2007) or various distance rings (Lazrak, Nijkamp, Rietveld, & Rouwendal, 2010;Noonan & Krupka, 2011), these studies have all found a premium associated with the proximity of an increasing number of historic landmarks. Similarly, Ahlfeldt and Maennig (2010c) using a range of distance, density and potentiality measures, find significantly positive effects associated with proximity to and variety of historic landmarks.…”
Section: Background and Existing Literaturementioning
confidence: 99%
“…Built cultural heritage provides an array of positive externalities and spillovers, ranging from visitors' attraction to a more general capacity of attracting high-human capital individuals with subsequent effect on regional growth (Falk et al, 2010) and cultivation of civic pride through preservation (Noonan, 2007). 1 Therefore it is not a surprise that the protection, maintenance and production of cultural heritage are common goals for many societies, in developed as well as developing countries (Snowball, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Interne und externe Preiseffekte wurden in zahlreichen in ternationalen Studien für denkmalgeschützte Gebäude nachgewiesen (z.B. Coulson, Lahr 2005;Coulson, Leichenko 2001;Noonan 2007). In Berlin zeigen sich positiveP reiswirkungen im Umkreis von600 mumBaudenkmäler.Der formale Akt der Unterschutzstellung zieht da bei keine signifikante Preiswirkung nachs ich, wasd arauf hindeutet, dass (a) Denkmalschutz als Proxy für bauliche Qualität herangezogen werden kann und (b) die mit der formalen Ei genschaft der Unterdenkmalschutzstellung ver bundenen (steuerlichenetc.)…”
Section: Gebauteumweltaus Stadtökonomischer Perspektiveunclassified